Determination of earthquake design criteria for fixed offshore platform (four-legged) due to Aceh earthquake in Malaysia - Lim, Jia Jun (2015)
The level of concern among civil engineers in Malaysia about the aspect to design the structural for earthquake design criteria is low. But there are some countries occur earthquake very often such as Aceh, Indonesia. Actually the tremors happened in Malaysia region due to Aceh earthquake and it also affected fixed offshore structure in Malaysia which the offshore structure in Malaysia are not designed to resist seismic loading. The objective of this study is to determine the earthquake design criteria for fixed offshore platform due to Aceh earthquake in Malaysia. The location of the fixed offshore platform is at the Terengganu. All the environmental factors data are given such as ranges of wave height and ground motion acceleration. The environmental loadings such as wave and wind load have been designed by referring API (American Petroleum Institute) design criteria. There are three types of analysis will be carry out: Free vibration analysis, Response spectrum analysis and Time history analysis. For the Free vibration analysis, there would have 12 mode shape of the structure. For the Response spectrum analysis, the analysis will be performed by using response spectra curves of EuroCode8. Time history analysis has been performed by referring to time history earthquake Aceh 2004. The computer software SAP2000 is selected to analyse this structure and the design code for the steel frame is EuroCode3. However, there is an assumption have been made when doing the 3D model of the structure. The fixed offshore platform structure is fixed to the ground instead of pilled and the soil interaction was neglected